PENERAPAN PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN DIRECT INSTRUCTION (DI) PADA POKOK BAHASAN LOGIKA DI SMKN 1 LUMAJANG KELAS XI PMS 1 TAHUN PELAJARAN 2012/2013 - Sukarti - (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2015)
The goal of research are: (1) To determine the effect of the use of the concept of the approach through the method of direct instruction to students' cognitive abilities and Mathematics (2) Looking for an alternative solution for effective learning. This research is using a class action research using three cycles. Each cycle consists of four phases: planing, action and observation, reflection, and revision. The subject of this research is a Class XI student of PMS 1 SMK Lumajang in 2012/2013. Data obtained in the form of a test results, observation sheet teaching and learning activities. Based on the analysis of the results of research and discussion can be drawn a conclusion that the Direct Instruction Lesson increase student performance that can be shown with the performance appraisal. Student achievement can be increased in Learning Direct Instruction. Increased learning achievement indicated by the results of student learning and the average value of the class.Keywords: Direct Instruction, academic achievement and student activity.